The power of significance how purpose changes your life - Maxwell, John C. 1947- (Center Street, 2017)
John C. Maxwell, #1 New York Times bestselling author, shows you how to achieve a life of purpose and significance in this compact new book derived from his previous title, Intentional Living. We all have a longing to be significant, to make a contribution, to be a part of something noble and purposeful. But many people wrongly believe that they have to have an amazing idea, be a certain age, have a lot of money, or be powerful or famous to make a real difference."--Publisher's description